Second Language Acquisition and Language Education-Bidirectional Synergies between Research and Practice - Martin Howard (MDPI AG, 2024)
This Special Issue brings together the fields of second language acquisition (SLA) and language education in an attempt to offer a venue for exploring mutual insights into classroom language learning [...]